Analysis of Causes and Evolution of Unemployment in Slovak Republic and its Influence on Enterprises - Kucharčiková, Alžbeta; Vodák, Jozef (Ekonomika, 2004)
This article is one of the outputs from authors’ activities in the scientific project “Diagnostics of input entities of transformation business processes”. This project is founded by a grant from the Scientific Grant Agency of the Ministry of Education of Slovak Republic and Slovak Academy of Sciences. This article is based on research work (in the year 2003), primarily in the Slovak Republic.